Pendampingan Penambahan Varian Rasa Sebagai Upaya Peningkatan Nilai Jual Produk UMKM Keripik Tempe “Nadhira” - Aan Zainal Muttaqin; Arista Eka Lestiana; Nala Rohmatul Aza (Lembaga Pengembangan Kinerja Dosen, 2025)
The Covid-19 pandemic has significantly impacted the income of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, prompting business actors to adapt through innovation, particularly in product variations. This study aims to enhance the marketability of